Perencanaan dan Perancangan Pusat Agroindustri Cokelat Desa Ekasari Kecamatan Melaya Kabupaten Jembrana: Bahasa Indonesia - Fabian, Arnoldus Made Dheo Virya; Linggasani, Made Anggita Wahyudi; Parwata, I Wayan; Gunawarman, Anak Agung Gede Raka (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2024)
The Ekasari Village Chocolate Agro-Industry Center has a role in improving the local economy and introducing abundant chocolate cultivation through the development of the cocoa industry. This research aims to provide a place for plantation farming activities, introduce good chocolate cultivation and meet food needs from the processed products of the Agroindustry Center. The analysis phase includes a site study, analysis of functions, users, and activities, and evaluation of harmony with the environment. The design method uses synthesis and evaluation to obtain the best alternative. The appearance of the building illustrates the concept of biomimicry and ecological themes through the use of wood and steel structures. The results show the use of ironwood as a construction material that is resistant to humid climates. The implementation of the external and internal layout refers to the needs of function and comfort, with the selection of materials that are in accordance with the theme and concept. It is expected that the Agroindustry Center will become a center of attention for cocoa farmers and the general public, and encourage the development of the local cocoa industry.